Asymmetric Redox‐Polymer Interfaces for Electrochemical Reactive Separations: Synergistic Capture and Conversion of Arsenic. Issue 6 (3rd December 2019) - Kim, Kwiyong; Cotty, Stephen; Elbert, Johannes; Chen, Raylin; Hou, Chia‐Hung; Su, Xiao
Abstract: Advanced redox‐polymer materials offer a powerful platform for integrating electroseparations and electrocatalysis, especially for water purification and environmental remediation applications. The selective capture and remediation of trivalent arsenic (As(III)) is a central challenge for water purification due to its high toxicity and difficulty to remove at ultra‐dilute concentrations. Current methods present low ion selectivity, and require multistep processes to transform arsenic to the less harmful As(V) state. The tandem selective capture and conversion of As(III) to As(V) is achieved using an asymmetric design of two redox‐active polymers, poly(vinyl)ferrocene (PVF) and poly‐TEMPO‐methacrylate (PTMA). During capture, PVF selectively removes As(III) with exceptional uptake (>100 mg As/g adsorbent), and during release, synergistic electrocatalytic oxidation of As(III) to As(V) with >90% efficiency can be achieved by PTMA, a radical‐based redox polymer. The system demonstrates >90% removal efficiencies with real wastewater and concentrations of arsenic as low as 10 ppb. By integrating electron‐transfer through the judicious design of asymmetric redox‐materials, an order‐of‐magnitude energy efficiency increase can be achieved compared to non‐faradaic, carbon‐based materials. The study demonstrates for the first time the effectiveness of asymmetric redox‐active polymers for integrated reactive separations and electrochemically mediated process intensification for environmental remediation. Abstract : Redox‐active polymer materials are exploited for the reactive separation of arsenic oxyanions. The molecular selectivity of a metallopolymer is combined with the electrocatalytic properties of a radical‐based organic electrode to achieve exceptional separation factors and redox‐mediated transformation. This work paves the way for advanced redox‐materials to be used in synergistic electrochemical processes for water purification, chemical and environmental process intensification, and electrocatalysis.